2013
DOI: 10.1080/10447318.2012.715990
|View full text |Cite
|
Sign up to set email alerts
|

How In-Home Technologies Mediate Caregiving Relationships in Later Life

Abstract: In-home technologies can support older adults' activities of daily living, provide physical safety and security, and connect elders to family and friends. They facilitate aging in place while reducing caregiver burden. One of older adults' primary concerns about in-home technologies is their potential to reduce human contact, particularly from cherished caregivers. In this exploratory in-situ study, we provided an ecosystem of networked monitoring technologies to six older adults and their caregivers. We analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
5
36
2
Order By: Relevance
“…Huber et al [6] identified that one of the most important factors that limits the adoption of technology by older adults is the fear that these systems might replace human contact with their family caregivers. Therefore, one plausible alternative to assist this group of people is to design meaningful experiences that do not limit physical exchanges with their caregivers.…”
Section: Related Workmentioning
confidence: 99%
“…Huber et al [6] identified that one of the most important factors that limits the adoption of technology by older adults is the fear that these systems might replace human contact with their family caregivers. Therefore, one plausible alternative to assist this group of people is to design meaningful experiences that do not limit physical exchanges with their caregivers.…”
Section: Related Workmentioning
confidence: 99%
“…* Prior work has explored the role of reporting sensor activity from older peoples homes into the homes of informal caregivers [10,27,26]. A barrier to the acceptance of such technologies has been the perception of privacy invasion [7] and concerns about reducing in-person contact with caregivers and family members [15]. We build upon this prior work by describing the findings from field trials of SHel (Safe Home Living), a pre-release commercial remote activity monitoring system to help relatives and friends check on older family members movements in their homes in a non-invasive (i.e., minimal impact upon the home environment) manner.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of an emergency, the technology can automatically alarm relatives or an emergency physician (Chiriac & Rosales, 2012). Moreover, these in-home technologies may have an influence on communication toward the elderly and could strengthen personal relationships (Huber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%